Design Strategy of the Sabes Study: Diagnosis and Treatment of Early HIV Infection Among Men Who Have Sex With Men and Transgender Women in Lima, Peru, 2013–2017. Issue 8 (7th March 2018) - Lama, Javier R; Brezak, Audrey; Dobbins, James G; Sanchez, Hugo; Cabello, Robinson; Rios, Jessica; Bain, Carolyn; Ulrich, Angela; De la Grecca, Robert; Sanchez, Jorge; Duerr, Ann
Abstract: The Sabes Study evaluated a treatment-as-prevention intervention among cisgender men who have sex with men and transgender women in Lima, Peru—populations disproportionately affected by the human immunodeficiency virus (HIV) epidemic. The intervention was designed to prevent onward transmission of HIV by identifying HIV-negative high-risk individuals, testing them monthly for the presence of HIV, and then rapidly treating those who became HIV-positive. The main outcome of interest was the development of a model predicting the population-level impact of early detection of HIV infection and immediate initiation of antiretroviral therapy in this population. From July 2013 to September 2015, a total of 3, 337 subjects were screened for HIV; 2, 685 (80.5%) were negative, and 2, 109 began monthly testing. We identified 256 individuals shortly after HIV acquisition, 216 of whom were enrolled in the treatment phase of the study. All participants were followed for 48 weeks (follow-up ended in 2017) and were then referred to the Peruvian Ministry of Health to continue receiving free HIV care and treatment. Initial findings from this intervention demonstrate that it is possible to recruit high-risk individuals, screen them for HIV, continue to test those who are initially HIV-negative in order to identify incident cases shortly after acquisition, and then rapidly link them to health care.